MEMAHAMI FUNGSI-FUNGSI MANAJEMEN SUMBERDAYA MANUSIA (MSDM) GUNA MENGOPTIMALKAN KINERJA PERUSAHAAN PELAYARAN - Sahudiyono Sahudiyono (Majalah Ilmiah Bahari Jogja, 2015)
Regarding the central role of human resources both for a corporation,and for the shipping company, human resource management should receiveserious attention so that the organization can optimally perform its efforts toachieve goals. As it is known that, human resources is one of the most strategicfactors of production, the company must build a climate of staffing which shouldbe structured, comprehensive and sustainable. Therefore the functions ofhuman resource management should be taken seriously by any company.By using a descriptive approach based on the study of variousmanagement literatures, this article provides an analysis of functions of humanresources management namely: 1) Human Resources Planning 2) Job Analysis,3) Recruitment and Selection, 4) Managing Performance, 5) Training andDevelopment, 6) Job Evaluation 7) Wages and Benefits, and 8) Relationshipsamong Employees